The importance of measuring psychosocial functioning in schizophrenia. - Brissos, S; Molodynski, A; Dias, V; Figueira, M (BioMed Central, 2011)
BACKGROUND: Schizophrenia is among the most disabling of mental illnesses and frequently causes impaired functioning. We explore issues of definition and terminology, and the relationship between social functioning, cognition, and psychopathology considering relevant research findings. METHODS: The present article describes measures of social functioning and outlines their psychometric properties. It considers their usefulness in research and clinical settings. Treatment aims and objectives are explored in the context of cognitive and social functioning. Finally, we identify areas for developing research and refining the measurement of social functioning. RESULTS: The definition and measurement of social functioning in schizophrenia remains a complex and disputed area. The relationships between symptoms, cognitive functioning and social functioning are complex but we are beginning to understand them better. Scales for measuring functioning in clinical practice must be brief and sensitive to change and the Personal and Social Performance (PSP) scale may offer several advantages in these regards. Brief cognitive assessments focusing upon the domains most commonly affected in schizophrenia, such as verbal memory and executive functions, should be coadministered with measures of functioning. CONCLUSIONS: The use of validated scales for schizophrenia that are sensitive to change over the course of the illness and its treatment, should allow for a better understanding of patients' functional disabilities, enabling better and more comprehensive monitoring and evaluation of both pharmacological and non-pharmacological treatment strategies.